2000
DOI: 10.1123/mcj.4.2.165
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Motor Equivalence in a Pointing Task Involving Locomotion

Abstract: A pointing task was performed both while subjects stood beside and while subjects walked past targets that involved differing movement amplitudes and differing sizes. The hand kinematics were considered relative both to a fixed frame of reference in the movement environment (end effector kinematics) and to the subject's body (kinematics of the hand alone). From the former view, there were few differences between standing and walking versions of the task, indicating similarity of the kinematics of the hand. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 21 publications
1
17
0
1
Order By: Relevance
“…It has been reported that there were no significant differences in the ground reaction forces when subjects visually "targeted" a force plate on a walkway and when they did not [20,21]. However, performing a task during walking has been shown to affect body kinematics, either during manual pointing tasks [22] or visual tasks [15,16]. For instance, subjects walking on a treadmill exhibit an 11% increase in knee flexion just after heel strike while reading 5-digit numbers on a computer screen positioned 4 meters away as opposed to simply staring at a dot at the same distance [16].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that there were no significant differences in the ground reaction forces when subjects visually "targeted" a force plate on a walkway and when they did not [20,21]. However, performing a task during walking has been shown to affect body kinematics, either during manual pointing tasks [22] or visual tasks [15,16]. For instance, subjects walking on a treadmill exhibit an 11% increase in knee flexion just after heel strike while reading 5-digit numbers on a computer screen positioned 4 meters away as opposed to simply staring at a dot at the same distance [16].…”
Section: Discussionmentioning
confidence: 99%
“…Trunk contribution to the reaching movement was examined using a methodology first reported by Marteniuk and colleagues (Marteniuk et al 2000;Marteniuk and Bertram 2001), which involved calculating the wrist coordinates from both world-centered and body-centered Significant differences between the two factors, condition and frame of reference, after post hoc analysis; where two conditions have the same superscript there was no significant difference for that variable frames of reference. This analysis revealed that children exhibited a different coordination between the trunk and arm in the three reach and grasp conditions.…”
Section: Discussionmentioning
confidence: 99%
“…To calculate the data relative to a dynamic, body-centered frame of reference, the trunk (sternum marker) coordinates were subtracted from the wrist coordinates. The latter allowed the determination of the extent to which the body movement contributed to the movement of the hand (Marteniuk et al 2000). Trunk contribution was quantified by calculating the excursion of trunk flexion/extension and trunk rotation.…”
Section: Dependent Measures Of Reaching Performancementioning
confidence: 99%
See 2 more Smart Citations